The Highlander's Irish bride - Kelly, Vanessa (Kelly, Vanessa. Clan Kendrick, 2021)
While being escorted by a handsome Highlander to a remote Scottish estate where her parents hope she will finally learn to behave like a proper lady, Miss Kathleen Calvert finds herself on a thrilling passion-filled adventure when their journey is besieged by danger.